2017
DOI: 10.1017/s0007123417000230
|View full text |Cite
|
Sign up to set email alerts
|

The Political Dynamics of Bureaucratic Turnover

Abstract: This Research Note explores the political dynamics of bureaucratic turnover. It argues that changes in a government’s policy objectives can shift both political screening strategies and bureaucratic selection strategies, which produces turnover of agency personnel. To buttress this conjecture, it analyzes a unique dataset tracing the careers of all agency heads in the Swedish executive bureaucracy between 1960 and 2014. It shows that, despite serving on fixed terms and with constitutionally protected decision-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 23 publications
2
44
0
Order By: Relevance
“…The demand for loyalty may be especially important when there is a partisan shift in government (e.g., Boyne et al ; Dahlström and Holmgren ; Meyer‐Sahling ; see also McCabe et al ). For instance, Dahlström and Holmgren () show that agency heads are considerably more likely to leave their posts following partisan shifts even in the presence of institutional systems designed to insulate the bureaucracy from political influence. In such circumstances, newly elected political principals may regard political patronage relationships with the previous political principal as a sign of disloyalty (i.e., a sign of misalignment with their visions, ideologies, and programs).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for loyalty may be especially important when there is a partisan shift in government (e.g., Boyne et al ; Dahlström and Holmgren ; Meyer‐Sahling ; see also McCabe et al ). For instance, Dahlström and Holmgren () show that agency heads are considerably more likely to leave their posts following partisan shifts even in the presence of institutional systems designed to insulate the bureaucracy from political influence. In such circumstances, newly elected political principals may regard political patronage relationships with the previous political principal as a sign of disloyalty (i.e., a sign of misalignment with their visions, ideologies, and programs).…”
Section: Theorymentioning
confidence: 99%
“…Unlike in the U.S. system, in which the incoming president can remove holdover political appointees from the previous regime at will upon entering office (Lewis ), many Western European democracies have adopted meritocratic recruitment regulations and stringent labor laws that insulate bureaucratic expertise from political control (Dahlström and Holmgren ; Huber ; Peters and Pierre ; Pollitt and Bouckaert ). The Korean system has implemented several measures resembling the European model.…”
Section: Institutional Background and Empirical Strategymentioning
confidence: 99%
“…What is sacrificed in scope is compensated for in internal credibility. Presidential transitions provide critical variation in agency preferences driven by turnover in both appointed and career personnel (Chen and Johnson 2014;Bolton, de Figueiredo, and Lewis 2017;Dahlström and Holmgren 2017), whereas the preferences of legislators within that narrow window are likely to be stable. 3 It also provides an important secondary contribution, since agency ideology is often thought of as a function of both an agency's "mission" and personnel.…”
Section: Interview With Authormentioning
confidence: 99%
“…More recently, scholars have started to systematically investigate the drivers of executive politicians' decisions to hire or fire senior officials in parliamentary contexts (Boyne et al 2010, Christensen, Klemmensen, and Opstrup 2014, Kopecký and Mair 2012, Kopecký et al 2016, Petrovsky et al 2017 as well as in the US (Hollibaugh, Horton, and Lewis 2014, Lewis and Waterman 2013, Ouyang, Haglund, and Waterman 2017. However, this research has two blind spots: First, as elaborated above, most scholars of parliamentary systems focus on partisan loyalty as dominating criterion for the (de)selection of officials (Dahlström and Niklasson 2013, Dahlström and Holmgren 2017, Ennser-Jedenastik 2014, 2016a, whereas only few authors consider other criteria such as professional qualifications or intra-governmental mobility (Fleischer 2016, Skans and Brösamle 2011, Veit and Scholz 2016).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Many existing studies find empirical support for the ally principle according to which executive politicians will prefer to work with bureaucrats with similar ideological preferences as they can delegate more discretion to them (Dahlström andHolmgren 2017, Huber andShipan 2006): For instance, affiliation with a governing party significantly increases the tenure of managers in Austrian state-owned enterprises (Ennser-Jedenastik 2014). An analysis of toplevel appointments in 16 West European countries revealed that politicians use partisan appointments to gain control over independent regulators (Ennser-Jedenastik 2016b).…”
Section: Partisan Loyaltymentioning
confidence: 99%